The principle underlying the wireless reference microphone enhancing noise reduction performance in multi-channel active noise control windows - Shen, Xiaoyi (2024)
Multi-channel active noise control (ANC) is widely applied as a practical approach to achieving a large noise cancellation area. However, the efficacy of the multi-channel ANC is significantly impacted by the quality of the reference signal in practice. Hence, we propose using wireless reference microphones in the multi-channel ANC, which substantially improves the reference signal quality and increases the noise reduction performance. Reference signal-to-interference ratio (RSIR) is brought for analysis to understand how the wireless multi-channel ANC system works. According to the theoretical derivation, the multi-channel adjoint least mean square (LMS) algorithm benefits from the higher RSIR that the wireless reference microphone brings about regarding steady-state performance. Furthermore, the numerical simulation and real-time experiments on a multi-channel ANC window in a resident room confirm these theoretical analyses.